Anticipating and planning for mine closure in South Africa. (January 2021) - Marais, Lochner; de Lange, Anri
Highlights: South African mining policy assumes that mining economies can diversify. Merafong City's economy declined by 3.2 % per annum, but the urban area grew by 35 %. Merafong City assumes economic diversification but downscaling makes it more dependent on mining. It is essential to anticipate and plan for decline and that this requires long-term aims. Abstract: Long-term planning must anticipate not just growth but the likelihood of decline. The international literature on shrinking cities is dubious about the wisdom of advocating permanency and suggests that a better approach to the problems of a resource-based city is to face the prospect of its shrinking and plan accordingly. We use a case study of Merafong City, a gold mining centre in Gauteng, to illustrate the unforeseen consequences of large-scale economic and population decline. Despite the decline in its mines, the city's footprint has expanded by 35 %. We argue that its problems stem from inappropriate post-apartheid policies, the power of the mining companies, the relaxation of planning legislation, a planning mindset that promotes growth, and a reluctance to plan for decline. We argue that in cities like this it is essential to anticipate and plan for decline and that this requires long-term aims that differ markedly from those of post-apartheid policy. We challenge the assumption of long-term economic growth in an uncertain industry dependent on global market forces.